2014
DOI: 10.1002/jsfa.6850
|View full text |Cite
|
Sign up to set email alerts
|

Crop load and harvest maturity effects on consumer preferences for apricots

Abstract: Management practices that increase fruit SSC and sugar/acid ratio, such as reducing crop load, will improve consumer satisfaction as long as fruit are harvested at an adequate maturity stage and are maintained in storage so that they do not soften too quickly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…TSS content values were slightly lower than those shown by other authors for other apricot cultivars, which were found to be in the range of 10-20 • Brix [11,28]. These differences may have been due to both the cultivar and the climatic conditions in the year of production, as well as management practices [5]. Our acidity values, however, were similar to those found by Ayour et al [29] in twelve apricot cultivars at different stages of maturity.…”
Section: Total Soluble Solids and Total Aciditysupporting
confidence: 61%
See 3 more Smart Citations
“…TSS content values were slightly lower than those shown by other authors for other apricot cultivars, which were found to be in the range of 10-20 • Brix [11,28]. These differences may have been due to both the cultivar and the climatic conditions in the year of production, as well as management practices [5]. Our acidity values, however, were similar to those found by Ayour et al [29] in twelve apricot cultivars at different stages of maturity.…”
Section: Total Soluble Solids and Total Aciditysupporting
confidence: 61%
“…According to Stanley et al [5], the TSS content of apricots was a determining factor in the sensory quality of fruits with higher firmness (over 15 N). This relationship between fruit quality parameters and consumer acceptance has been reported in other stone fruit, where acceptability does not depend on a single parameter but on the interaction of several [26,35].…”
Section: Sensory Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Too much firmness is, therefore, inappropriate because consumers are primarily looking for sweetness, flavor, and fondant criteria [50]. is balanced relationship between the sugar and acid contents is very important on the quality of apricot fruits, as it was already reported in previous studies [22,51,52]. It made it possible to highlight all the sensory attributes and to discriminate apricots organoleptic quality.…”
Section: Correlations Between Sensory Perception and Biochemical Traitsmentioning
confidence: 99%